Association between catheter ablation and psychiatric disorder risk in adults with atrial fibrillation: a multi-institutional retrospective cohort study - Liu, Ting-Hui; Wu, Jheng-Yan; Huang, Po-Yu; Hsu, Wan-Hsuan; Chuang, Min-Hsiang; Tsai, Ya-Wen; Hsieh, Kuang-Yang; Lai, Chih-Cheng (Frontiers in Psychiatry, 2025)
BackgroundGiven that atrial fibrillation (AF) s associated with a high risk of psychiatric disorders, understanding the potential benefits of catheter ablation is clinically significant. This study was conducted to examine whether catheter ablation can prevent psychiatric disorders in patients with AF.MethodsA retrospective cohort study was conducted over two years using data from the TriNetX electronic health record network. The study included adults diagnosed with AF and treated with either antiarrhythmic or rate-control medications. Participants were divided into two groups: those who underwent catheter ablation and a control group without ablation. The primary outcome measured was a composite of anxiety, depression, and insomnia occurrence within one to three years post-treatment. Secondary outcomes included individual psychiatric disorders, suicidal ideation or attempts, dementia, cerebral infarction, and atopic dermatitis (as a negative control).ResultsWe included 21,019 patients in each matched group. The ablation group demonstrated a lower risk of the primary combined outcome (hazard ratio(HR):0.873, 95% confidence interval (CI) 0.784–0.973, p<0.01), and secondary outcomes including anxiety (HR:0.822, 95% CI:0.700–0.964; p=0.016), depression (HR:0.614, 95% CI:0.508–0.743; p<0.001), suicidal ideation or attempts (HR:0.392, 95% CI:0.165–0.934; p=0.028), dementia (HR:0.569, 95% CI:0.422–0.767; p<0.001), and cerebral infarction (HR:0.704, 95% CI:0.622–0.797; p<0.001) compared to the non-ablation group.ConclusionsIn patients with atrial fibrillation, catheter ablation was associated with a reduced risk of developing psychiatric disorders, including anxiety, depression, insomnia, suicidal ideation or attempt, and dementia, in comparison to those who did not undergo ablation. Clinicians should consider incorporating psychiatric risk factors into their comprehensive patient assessment when evaluating candidates for catheter ablation.